A Comparative Study on Public Administration Values: Using Changing Doctrines in Interpreting Diversity in Contents of Public Administration Values - Kaustinen, Anna (My University, 2008)
Ethics and values are one of the enduring questions of humanity. They treat issues that cover both ideal and practice in guiding the human life on individual as well as collective level. Much of the current research in the field of administrative sciences has been focused on ethics and this study follows the line of research. This research examines public administration values and aims to understand their changing nature. The primary research problem is that what can be distinguished as public administration values and furthermore, what issues the selected public administration doctrines emphasize in terms of these values. It is supposed that a change in doctrines reveals the changes in values. Doctrines as ways of getting organized also highlight the public administration culture. The third research question asks how do the doctrines explain countries practice-oriented codes of ethics. The examination covers such three countries as France, the United Kingdom and Finland. This research conducts a comparative study on the differences of public administration values and presumes an analogy between public administration doctrines and values. Multiple cases comparison compares Bureaucratic, Management and Service values. The methodology of this research is based on hermeneutics and the aim is to interpret the public administration values. Qualitative method then seeks to understand and explain phenomena. This research conducts a secondary analysis on data that is collected from various documents, scholarly journals and scientific publications. The public administration has its distinguishing character and identity that is the culture. Public administration culture fosters special values that are invisible but that manifest among others in visible practices and documents. In most cases, values have to do with preferable outcome or way of acting. The public administration values are considered to be changing. The change stems from broad historical change as well as changing environment, the introduction of reforms and changes in the public administration culture. The public administration value change has to do with changing doctrines since they view the public administration culture differently. The research indicated that the doctrines provided a distinctive framework for public administration values. Bureaucratic, Management and Service values held different preferences and led to diverse interpretations. The practice-oriented examination of codes of ethics revealed the ambiguous and multilayered nature of values. In practice different values coexisted simultaneously. Public administration value change meant the existence of both old and new values in the organization of values. It was noted that different values must be aligned and in order since value conflict could cause the reorganization of the value system and value change. Present value expressions consisted of different preferences and justifications and it was suggested that the existence of different values should only multiply in the future.
Keywords: value; public administration; doctrine; change; comparison; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|